A Structural Equation Modeling Analysis of the Model of Motivational Variables Affecting Iranian EFL Teachers’ Competency in ELT - Khalil Sazideh; Shahram Afraz; Fazlolah Samimi (Iranian Evolutionary Educational Psychology Journal, 2019)
Teacher competency is defined as an integrated set of personal characteristics, knowledge, skills and attitudes that are needed for effective performance in various teaching contexts. Despite the importance of teachers’ competency in the design of classroom practices and methods, few studies in Iranian EFL context have explored the effects of factors affecting this construct. Accordingly, the present study attempted to develop and test a model of motivational variables affecting a group of Iranian EFL teachers’ competency by using Structural Equation Modeling (SEM) approach. A total of 197 EFL teachers teaching at a number of schools in Hormozgan province participated in the study and completed a teacher competency test, a self-efficacy beliefs scale and a self-regulation in teaching questionnaire. The tested model gave satisfactory fit indexes and the variables of study had a positive relation with teachers’ competency. More specifically, instructional strategy, as the subscale of self-efficacy, and intrinsic interest, as the subcomponent of self-regulation, could best predict teachers’ competency.